1997
DOI: 10.1152/jappl.1997.83.6.2086
|View full text |Cite
|
Sign up to set email alerts
|

Bed rest suppresses bioassayable growth hormone release in response to muscle activity

Abstract: McCall, G. E., C. Goulet, R. E. Grindeland, J. A. Hodgson, A. J. Bigbee, and V. R. Edgerton. Bed rest suppresses bioassayable growth hormone release in response to muscle activity. J. Appl. Physiol. 83(6): 2086–2090, 1997.—Hormonal responses to muscle activity were studied in eight men before (−13 or −12 and −8 or −7 days), during (2 or 3, 8 or 9, and 13 or 14 days) and after (+2 or +3 and +10 or +11 days) 17 days of bed rest. Muscle activity consisted of a series of unilateral isometric plantar flexions, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 20 publications
7
37
2
Order By: Relevance
“…The lack of an acute increase in GH follows our previous work on the GH response to acute resistance exercise using the rat tibial line bioassay [7][8][9]. However, these results differ from the work of McCall and co-workers [10,11] who twice reported that unilateral plantar flexion exercise increased GH as measured by the rat tibial line assay. These very different exercise protocols might explain this discrepancy in findings as they resulted in divergent cortisol responses.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The lack of an acute increase in GH follows our previous work on the GH response to acute resistance exercise using the rat tibial line bioassay [7][8][9]. However, these results differ from the work of McCall and co-workers [10,11] who twice reported that unilateral plantar flexion exercise increased GH as measured by the rat tibial line assay. These very different exercise protocols might explain this discrepancy in findings as they resulted in divergent cortisol responses.…”
Section: Discussionsupporting
confidence: 72%
“…AHRET caused a significant increase in circulating cortisol [4,6] which is an inhibitor of bone growth [23]. In contrast, the protocol used by McCall et al [10] induced either no change or a decrease in cortisol pre-to post-exercise. Alternately, gender differences might explain the discrepancy in the bioactive GH response to exercise as measured by the rat tibial line assay.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations